Post-COVID Syndrome in Bipolar Affective Disorder Patient - Firdaus, Ahmad; Dwiputri, Adelita Vega; Irkadiratna, Aderisti; Nugraha, Adi Satria; Narulitia, Adinda; Prasetya, Era Catur; Secka, Absa; Muslih, Muhammad (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Post-COVID is a multifactorial disease that describes the residual effects of acute COVID-19 infection that are continuous or relapsing and in remission. The study found that 87% of people who recovered and were discharged from the hospital showed persistence of at least one symptom even within 60 days. COVID-19 patients who have bipolar disorder require therapeutic adjustments to avoid specific drug interactions between psychotropic drugs and those used in COVID-19 protocols. Objective: To determine the treatment of post-COVID patients with bipolar affective disorder.Methods: Collect and analyze research articles on Update Therapy for Post-COVID Syndrome Patients with Bipolar Affective Disorder. These articles were obtained by searching using Google Scholar, PubMed/NCBI, and SAGE Journal. Results: The use of combination drugs between antipsychotics and antidepressants with hydroxychloroquine/azithromycin is not recommended because it has side effects that can induce psychiatric symptoms. COVID-19 patients with bipolar disorder (BD) who do not respond to pharmacotherapy may receive electroconvulsive therapy (ECT). Non-pharmacological therapies such as counseling and the use of telepsychiatry are effective in treating mental health and overcoming adverse psychological effects.Conclusion: COVID-19 patients with bipolar affective disorder require unique therapy to avoid drug interactions and pharma-cotherapy. Non-pharmacological efforts include counseling and telepsychiatry to cope with emotional distress and mental health challenges. However, challenges remain in providing care for these patients.